Political communication - Foster, Steven (Politics study guides., 2010)
This introduction to the study of political communication covers the following subjects:*The history of the media in the UK and the USA including the concentration of ownership and the emergence of new media technologies*The relationship between the media and political parties, especially the effect the media has had on the policies and internal power structures of parties and other organisations such as pressure groups*Media influence on the electorate and the conduct of democratic politics*The constitutional significance of the politics of the mediaThe first part of the book focuses on the s.